1989
DOI: 10.1159/000138610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tin-Porphyrins on Developmental Changes in Hepatic Cytochrome P450 Content, Selected P450-Dependent Drug-Metabolizing Enzyme Activities and Brain Glutathione Levels in the Newborn Rat

Abstract: Sn-mesoporphyrin is considerably more effective than Sn-protoporphyrin in inhibiting bilirubin production in vivo, in the experimental animal. In this study the effects of Sn-mesoporphyrin, administered in doses ranging from 1 to 20 μmol/kg b.w., on the developmental patterns of hepatic cytochrome P450 content and cytochrome P450-dependent drug metabolism in rat neonates were examined at various time points during the 5-week period immediately after birth. No detrimental alterations in cytochrome P450 content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…To further ascertain the characteristics of the expressed HO protein, we tested the effect of Sn-mesoporphyrin, a potent inhibitor of HO activity, on microsomal preparations from both nontransfected and transfected cells. Addition of 5 ,uM Sn-mesoporphyrin to cell preparations inhibited the enzyme activity by -90% and -75% (P < 0.001) in both control and transfected cells, respectively (Table 1), as has been demonstrated with the normal and induced mammalian HO (24)(25)(26)(27)(28).…”
Section: Resultssupporting
confidence: 59%
“…To further ascertain the characteristics of the expressed HO protein, we tested the effect of Sn-mesoporphyrin, a potent inhibitor of HO activity, on microsomal preparations from both nontransfected and transfected cells. Addition of 5 ,uM Sn-mesoporphyrin to cell preparations inhibited the enzyme activity by -90% and -75% (P < 0.001) in both control and transfected cells, respectively (Table 1), as has been demonstrated with the normal and induced mammalian HO (24)(25)(26)(27)(28).…”
Section: Resultssupporting
confidence: 59%
“…However, efforts to detect changes in iron using Perl' s stain or 3,3 '-diaminobenzidine-enhanced Pen's stain have been unsuccessful to date, most likely because of the low sensitivity of these methods (data not shown). Our data do not preclude other potentially important protective mechanisms, including alterations in cytochrome P450 and cytochrome P450-dependent enzymes (Drummond et al, 1989;Sessa et al, 1989) and the inhibition of soluble guanylyl cyclase, a property of both metalloporphyrin heme oxygenase inhibitors (Ignarro et al, 1984;Luo and Vincent, 1994) and MnTMPyP (Pfeiffer et al, 1998). Protection against H2O2 by combined tin-mp and MnTMPyP was partial, suggesting that cell injury from H2O2 involves mechanisms not sensitive to either tin-mp or MnTMPyP.…”
Section: Discussionmentioning
confidence: 59%
“…Mps have been found to also interact with other heme-containing enzyme systems, such as nitric oxide synthase (NOS; Luo and Vincent, 1994; Meffert et al, 1994), soluble guanylyl cyclase (sGC; Ignarro et al, 1984; Grundemar and Ny, 1997), and cytochrome P450 (CYP 450 ; Drummond et al, 1989; Trakshel et al, 1992). They also affect hematopoiesis (Maines and Trakshel, 1992b; Lutton et al, 1997), steroidogenesis (Maines and Trakshel, 1992b; Drummond et al, 1996), and the iron status of the body (Kappas et al, 1993; Berglund et al, 1999).…”
Section: Pharmacodynamics Of Metalloporphyrinsmentioning
confidence: 99%
“…Others showed that hepatic CYP 450 content is only transiently altered after administration of SnPP or SnMP to neonatal rats and does not persist into adulthood. The studies used several different doses and application routes to adult or neonatal rats (Drummond et al, 1989, 1996). Overall, SnPP and SnMP decrease CYP 450 activity and thus affect CYP 450 -dependent enzymes of adrenal synthesis and drug metabolism in animal models.…”
Section: Pharmacodynamics Of Metalloporphyrinsmentioning
confidence: 99%